Motor sequencing abnormalities are the trait marking neurological soft signs of schizophrenia (2015)
We describe the profile of NSS across the one-year course of schizophrenia in 84 Nigerian first-episode patients. They were assessed at baseline and 3 monthly for 12 months using the Neurological Evaluation Scale and the Positive and Negative Syndrome Scale (PANSS), and treated with flupenthixoldecanoate. The patternofNSStotalandsub-categoryscoresobtainedfromrepeatedmeasurementswereinvestigatedfor responders (≥50% reduction of baseline PANSS scores) and non-responders using the method of repeated measures analysis of variance. Trait-like features of NSS categories were quantified using intra class correlation coefficients (ICCs). NSS were present in 96.4% of the patients at baseline (mean 21.5±11.1). The motor-sequencing sub-category was found unrelated to changes in schizophrenia psycho pathology with treatment (positive, r=0.19, p=0.136., negative, r=0.12, p=0.350; disorganization, r=0.16, p=0.245; overall, r=0.20, p=0.112). Regardless of decrements in psychopathology, motor-sequencing scores remained relatively unchanged across the course of the disease (main effects: responders’ F=2.44, p=0.930, ‘poor responders’ F=0.27, p=0.764, entire sample F=1.87, p=0.160). ICC was “substantial” at 0.8 (95% C. I=0.6–0.9). Only the motor-sequencing NSS appear to be trait marker of schizophrenia in this sample. Other NSS seem to reflect symptomatic states of the disorder.